Integrating Indigenous Agricultural Knowledge with Modern Practices for Sustainable Farming and Food Security (Journal of Agriculture and Biology, 2025)
Farmers can achieve sustainable farming by using Modern Agricultural Practices (MAP) and Traditional Ecological Knowledge (TEK). Researchers perform a study to evaluate how TEK-MAP integrates with farming systems by conducting surveys and conducting semi-structured interviews along with performing field observations. The research gathers quantitative findings from survey data and qualitative results from interviews through a mixed techniques approach. TEK-MAP adoption exists in three levels with 45% of farmers implementing the system completely and the rest integrating it partially or not at all. Three main barriers that prevent TEK-MAP adoption stem from insufficient institutional backing and monetary difficulties as well as deficiencies in laws. The research shows widespread adoption of intercropping systems and agroforestry and organic pest control methods belonging to TEK while MAP includes precision farming and irrigation systems and biotechnology generates efficiency. The onsite verification shows both approaches together create healthier soil together with better water reserve and financial viability. This research reveals the necessity of developing policy measures together with training sessions and financial backing to boost TEK-MAP usage for sustainable farming.